PROVERBS AS AN OBJECT OF LINGUISTIC RESEARCH (Multidisciplinary Journal of Science and Technology, 2025)
This article provides important insights into the significance of proverbs in modern cognitive linguistics. Additionally, it analyzes the most precise and general definitions of the concept of “proverb” based on the opinions of several linguists who have conducted research in this field. The article also explores the differences between proverbs and sayings, the unique characteristics of proverbs, and their importance as an object of philological research.